The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1502-3885.2011.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance of Norway spruce (Picea abies) onto mafic Lommoltunturi fell in Finnish Lapland during the last 200 years

Abstract: As a result of global changes, shifts of alpine tree lines towards higher elevations have been recorded, but the role of the spatial variability of the snowpack and zonal‐pattern soil‐nutrient regimes is poorly understood. Norway spruce (Picea abies (L.) Karst) is best suited to fertile soils, and hence we applied soil physical‐chemical and snow measurements and the age chronology of Norway spruce along an elevational gradient (380–557 m a.s.l.) to address a vertical soil zonality hypothesis on mafic Lommoltun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It is generally accepted that, at larger spatial and temporal scales, growing season temperature is the key factor defining the tree line position (Holtmeier 2003;Körner 2012). At shorter and more local scales, tree line responses to climate change may be modulated by factors such as wind, precipitation, snow cover, geomorphology, soil development and biotic interactions, sometimes operating in a non-linear manner (Körner & Paulsen 2004;Kullman 2007b;Kullman & Öberg 2009;Elliott & Kipfmueller 2010;Holtmeier & Broll 2010;Paus 2010;Malanson et al 2011;Mathisen & Hofgaard 2011;Kirdyanov et al 2012;Sutinen et al 2012;Takahashi et al 2012). In addition, it is impossible to rule out the possibility that climatic requirements and tolerances have changed during the postglacial period (cf.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally accepted that, at larger spatial and temporal scales, growing season temperature is the key factor defining the tree line position (Holtmeier 2003;Körner 2012). At shorter and more local scales, tree line responses to climate change may be modulated by factors such as wind, precipitation, snow cover, geomorphology, soil development and biotic interactions, sometimes operating in a non-linear manner (Körner & Paulsen 2004;Kullman 2007b;Kullman & Öberg 2009;Elliott & Kipfmueller 2010;Holtmeier & Broll 2010;Paus 2010;Malanson et al 2011;Mathisen & Hofgaard 2011;Kirdyanov et al 2012;Sutinen et al 2012;Takahashi et al 2012). In addition, it is impossible to rule out the possibility that climatic requirements and tolerances have changed during the postglacial period (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Kalliola 1973;Sutinen et al 2002Sutinen et al , 2012Närhi et al 2011) and the concentrations of plant elements generally reflect the element composition of the bedrock beneath the growing site (Närhi et al 2013). It has been shown that the forest vegetation communities of Finnish Lapland are intimately related to soil chemistry; Ca-concentration being the major variable in determining plant diversity (Närhi et al 2011).…”
Section: Moose Damage Was Concentrated In the Areas Of Nutrient-rich mentioning
confidence: 99%
“…One explanation for this can be that the till in the upper slopes of fells have lower concentrations of Ca and Mg than lower slopes (Sutinen et al 2012). This partly co-incides with the finding of Nikula et al (2008) who found that the concentration of soil-exchangeable Mg was a significant variable in the assessment of moose damage risk.…”
Section: Moose-damaged Stands Mainly Located In Subaquatic Areas and mentioning
confidence: 99%
“…With regard to a significant increase of stem numbers, growth conditions near tree and timber lines seem to be favourable enough to enhance seeding, seedling establishment and survival of trees of all age classes. Supposing that prolonged growing seasons as well as higher temperatures in summer and winter times are at least partly responsible for the observed development, a northward and upward transition of spruce forest line can be expected where the geological factors, such as nutrient supply, allow this (Hyppönen et al 2003;Sutinen et al 2012).…”
Section: Discussionmentioning
confidence: 99%